Synthesis and Staphylococcus aureus biofilm inhibitory activity of indolenine-substituted pyrazole and pyrimido[1,2-b]indazole derivatives - Yap, Cheng Hong; Abdul Qaiyum, Ramle; Lim, See Khai; Avinash, Rames; Tay, Sun Tee; Chin, Sek Peng; Kiew, Lik Voon; Tiekink, Edward R. T. *; Chee, Chin Fei (Elsevier, 2023)
Staphylococcus aureus is a highly adaptable opportunistic pathogen that can form biofilms and generate persister cells, leading to life-threatening infections that are difficult to treat with antibiotics alone. Therefore, there is a need for an effective S. aureus biofilm inhibitor to combat this public health threat. In this study, a small library of indolenine-substituted pyrazoles and pyrimido[1,2-b]indazole derivatives were synthesised, of which the hit compound exhibited promising antibiofilm activities against methicillin-susceptible S. aureus (MSSA ATCC 29213) and methicillin-resistant S. aureus (MRSA ATCC 33591) at concentrations significantly lower than the planktonic growth inhibition. The hit compound could prevent biofilm formation and eradicate mature biofilms of MSSA and MRSA, with a minimum biofilm inhibitory concentration (MBIC50) value as low as 1.56 µg/mL and a minimum biofilm eradication concentration (MBEC50) value as low as 6.25 µg/mL. The minimum inhibitory concentration (MIC) values of the hit compound against MSSA and MRSA were 50 µg/mL and 25 µg/mL, respectively, while the minimum bactericidal concentration (MBC) values against MSSA and MRSA were > 100 µg/mL. Preliminary structure-activity relationship analysis reveals that the fused benzene ring and COOH group of the hit compound are crucial for the antibiofilm activity. Additionally, the compound was not cytotoxic to human alveolar A549 cells, thus highlighting its potential as a suitable candidate for further development as a S. aureus biofilm inhibitor.